POTENSI DAN PETA KONFLIK PADA PILKADA ACEH TAHUN 2017 - Mumtazinur - Mumtazinur (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2019)
This article is an effort to explain the potention of conflict and the correlation to the map of conflict. It begins by a brief several cases of violence or riots that occurred before the election. this paper also describes the forms of violence that occurred during regional elections in Aceh. besides, this paper also tries to provide a solution to the conditions that occur or as a preventative measure for similar cases in the future